Distribution, host plant association, and morphological diagnosis of adults and larvae of Haplothrips biroi (Thysanoptera: Phlaeothripidae) - Balcerčík, Jozef; Kucharczyk, Halina; Mešková, Michaela; Zvaríková, Martina; Masarovič, Rudolf; Fedor, Peter (Zootaxa, 2025)
Haplothrips biroi (Priesner) is known from several southern European countries and is here newly recorded from southwestern Slovakia. The host plant is confirmed as Ballota nigra [Lamiaceae], with 107 female and 25 male adults collected, and the species successfully reared on the host leaves. Key morphological features of adults and larvae are illustrated, and the ecological implication of the record briefly discussed.